Patient’s perceived empathy can predict doctor-patient relationship in medical interaction - Caixia Han; Qing Wu; Chenchen Liu; Pei Wang (BMC Medical Education)
Abstract Background Patient perceived empathy plays a major role in establishing a good doctor–patient relationship. Therefore, this study explores the relationship among patient perceived empathy, quality of doctor-patient communication, and evaluation of the doctor-patient relationship while initially investigating the possible factors influencing patient perceived empathy. Methods We used the C-CARE scale, the C-SEGUE framework, and the C-PDRQ-15 scale to measure patient perceived empathy, ratings of doctor-patient communication quality, and ratings of patient-doctor relationships, respectively. A nationwide survey was conducted among 3039 patients, aged 18 to 92 years in China. Bootstrapped mediation analysis was performed. Results The age of the patient, the grade of hospital, and the consultation duration have significant differences in the scores of patient perceived empathy. There was a significantly positive correlation among patient's perceived empathy, doctor-patient communication, and doctor-patient relationship. Patient's perceived empathy can not only directly predict doctor-patient relationship , but also predict doctor-patient relationship through the mediating effect of doctor-patient communication. Conclusion Patient perceived empathy was related to age, hospital grade, and consultation duration. Patient perceived empathy can improve the doctor-patient relationship directly and can also optimize it indirectly via doctor-patient communication. The more empathy patients feel during medical interactions, the more positive their evaluation of the doctor-patient communication process and the more harmonious the doctor-patient relationship will be. Practice implications Emphasizing the importance of empathy in clinical encounters can facilitate effective doctor-patient communication and hence strengthen the doctor-patient relationship. Respecting and understanding patients is more important than providing professional medical advice when conveying empathy.